Cyber Security Analysis and Protection of Wireless Sensor Networks for Smart Grid Monitoring - Daojing He; Chan, Sammy; Mohsen Guizani (IEEE wireless communications, 2017)
In order to overcome the limitations of traditional monitoring technologies (e.g., those relying on wired networks), more and more real-time status monitoring systems based on wireless sensor networks (WSNs) are employed in smart grids to provide a strong service guarantee for monitoring and communication of electrical grids. With the use of wireless communication channels and possible deployment in harsh environments or unattended areas, they are subject to many types of attacks. Also, there are some limitations on deployed security mechanisms in these environments. Therefore, such systems are vulnerable to cyber security risks. This article carries out a comprehensive analysis of such a specific application environment, providing the risk classification and security assessment for such systems.